STRATEGI DAKWAH MUI (MAJELIS ULAMA INDONESIA) JAWA TENGAH MELALUI SERTIFIKASI HALAL - Asri Wahyuningrum; H. Anasom; Thohir Yuli Kusmanto (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2015)
Halal product is part of responsibility muslims consumer by industrial. Halal product assurance based on majesty, who society have the right informations, clearly, and completely. This research aim is determine the certification of halal as a da’wa strategies of MUI Central Java and also supporting and inhibiting factors there. This Research used qualitative research using management of da’wa approach. The data were collected through techniques: interview, observation, and documentation. The data analysis are data: reduction, verification, and conclusion. The result of this research: there are two da’wa strategies used LPPOM MUI which on program Gerakan Masyarakat Sadar Halal